Ethics of Islamic Financial Transactions - Abu Bakar, Azizi; Said Aladwan, Reyadh Nofan; Zainal, Hafizah (International Journal of Psychosocial Rehabilitation, 2019)
Ethics are the crucial elements of Islamic law. They have a huge impact on the development of Islamic society and its morals. Islamic ethics help regulate the internal affairs between members of the Muslim community in an organized manner, and affairs with non-Muslim communities. As a result, Islamic morality has been given careful attention in this research. It is not however limited to general matters rather exceeded even further, making the provisions of Islamic law mandatory for all contracts in Islam.